Assessing Staffing Needs in the Maintenance Department of a Tertiary Care Teaching Hospital Using Workload Analysis - Alvita Lurdin Saldanha; Shyni Cardoza; Jyothi Seema Moras; Sonal Sophia Fernandes (RGUHS Journal of Allied Health Sciences)
Background Effective staffing in hospital maintenance departments is crucial for ensuring smooth operation of healthcare facilities and maintaining high-quality patient care. However determining optimal staffing levels can be challenging due to various factors such as workload fluctuations skill mix and budget constraints.Objective This research aimed to provide a comprehensive assessment of staffing needs in the hospital maintenance department by conducting a workload analysis and applying insights from these studies ultimately contributing to improved operational efficiency and patient care.Methods Data was collected from 03062024 to 09062024 through direct interviews with staff to assess current work processes biometric attendance reports and other relevant sources.Results The study findings indicate that the maintenance departments actual working hours 9.24 hours day exceed the desired working hours 7.5 hoursday resulting in overtime work 1.7-2 hoursday which affects employee well-being productivity and efficiency. Moreover the staffing analysis revealed a significant shortage of staff with 23 additional personnel required to meet workload demands. Conclusion This report highlights the critical need for additional staff in the maintenance department to address workload demands and prevent adverse outcomes ensuring improved operational efficiency and patient care.